Computational model of stent-based delivery from a half-embedded two-layered coating. Issue 12 (9th September 2020) - , Sarifuddin; Roy, Somnath; Mandal, Prashanta Kumar
Abstract: An attempt is made in the present investigation to develop a computational model for the purpose of studying the effect of interstitial flow in the porous media on the distribution of drug eluted from a half-embedded drug-eluting stent and its retention in the presence of two-layered coating of the stent. The transport of free drug inside the coatings is considered as an unsteady diffusion process while that in the tissue as an unsteady convection–diffusion–reaction process. The bound drug is governed by an unsteady reaction process only. Immersed boundary method (IBM) in the staggered grid formulation, popularly known as marker and cell (MAC) method, has been leveraged to tackle numerically the governing equations. This model highlights the benefits of consideration of two-layered coating and does predict underlying mechanism for better efficacy by tweaking the kinetics parameters. Comparisons are also made with the results available for stent-based delivery.